Insider trading law enforcement and gross spreads of ADR IPOs - Chen, Hsuan-Chi; Hao, (Grace) Qing (Journal of Banking & Finance, 2011)
Using American Depositary Receipt (ADR) IPOs from 34 countries during 1980–2004, we find that, on average, the enforcement of insider trading laws reduces the underwriter gross spread by 49–61 basis points, which is about 10–12% of the average gross spread for ADR IPOs. This relation is present regardless of whether issuers have a prior listing or whether issuers are from developed or emerging markets. The association becomes stronger for ADRs underwritten by less prestigious underwriters and for issuers that are involved in privatization. The political institutions in the issuers’ home markets also affect gross spreads.